Ekeland’s Variational Principle for Functions Unbounded from below - Sengupta, R.; Zhukovskiy, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
A modification of the Ekeland variational principle for functions unbounded from below is obtained. For a wide class of differentiable functions not necessarily bounded below, it is shown that there exists a minimizing sequence satisfying the first-order necessary conditions, up to any desired approximation.